Adult skin-derived precursor Schwann cell grafts form growths in the injured spinal cord of Fischer rats. (20th February 2018) - May, Zacnicte; Kumar, Ranjan; Fuehrmann, Tobias; Tam, Roger; Vulic, Katarina; Forero, Juan; Lucas Osma, Ana; Fenrich, Keith; Assinck, Peggy; Lee, Michael J; Moulson, Aaron; Shoichet, Molly S; et al.
Abstract: In this study, GFP + skin-derived precursor Schwann cells (SKP-SCs) from adult rats were grafted into the injured spinal cord of immunosuppressed rats. Our goal was to improve grafted cell survival in the injured spinal cord, which is typically low. Cells were grafted in hyaluronan-methylcellulose hydrogel (HAMC) or hyaluronan-methylcellulose modified with laminin- and fibronectin-derived peptide sequences (eHAMC). The criteria for selection of hyaluronan was for its shear-thinning properties, making the hydrogel easy to inject, methylcellulose for its inverse thermal gelation, helping to keep grafted cells in situ, and fibronectin and laminin to improve cell attachment and, thus, prevent cell death due to dissociation from substrate molecules (i.e., anoikis). Post-mortem examination revealed large masses of GFP + SKP-SCs in the spinal cords of rats that received cells in HAMC (5 out of n  = 8) and eHAMC (6 out of n  = 8). Cell transplantation in eHAMC caused significantly greater spinal lesions compared to lesion and eHAMC only control groups. A parallel study showed similar masses in the contused spinal cord of rats after transplantation of adult GFP + SKP-SCs without a hydrogel or immunosuppression. These findings suggest that adult GFP + SKP-SCs, cultured/transplanted under the conditions described here, have a capacity for uncontrolled proliferation. Growth-formation in pre-clinical research has also been documented after transplantation of: human induced pluripotent stem cell-derived neural stem cells (Itakura et al 2015 PLoS One 10 e0116413), embryonic stem cells and embryonic stem cell-derived neurons (Brederlau et al 2006 Stem Cells 24 1433–40; Dressel et al 2008 PLoS One 3 e2622), bone marrow derived mesenchymal stem cells (Jeong et al 2011 Circ. Res. 108 1340–47) and rat nerve-derived SCs following in vitro expansion for >11 passages (Funk et al 2007 Eur. J. Cell Biol. 86 207–19; Langford et al 1988 J. Neurocytology 17 521–9; Morrissey et al 1991 J. Neurosci. 11 2433–42). It is of upmost importance to define the precise culture/transplantation parameters for maintenance of normal cell function and safe and effective use of cell therapy.